Interlanguage syntactic temporary, permanent, and fossilized errors in second language writing - Andi Rustandi; R. Bunga Febriani; Maria Teresa Asistido; Syafryadin Syafryadin (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
Although writing argumentative essays has been widely investigated, limited research has focused on types of syntactic fossilization errors, let alone in doctoral students of English department contexts. This study investigated the interlanguage temporary, permanent, and fossilized errors in the second language writing of seven doctoral students from one private university in Jakarta, Indonesia. The study employed a linguistics content analysis method using the argumentative essay products taken from the course of Lexicology and Lexicography during one semester. The data were analyzed using the framework of four syntactic fossilization errors: verb omission, subordination, double verb, and passive voice. In addition, inter-rater reliability was used to measure the trustworthiness of fossilized error analysis in students' argumentative essays. The findings revealed that the doctoral students made four fossilized errors: subordination, omission, double verb, and passive voice. However, verb omission and sub-ordination emerged as temporary fossilization errors and a double verb and passive voice as permanent syntactic fossilization errors in writing argumentative essays. This result suggests that doctoral students need a bridging course to reduce all kinds of errors in writing an argumentative essay as the requirements before they join the real classroom.